Excellent corrosion resistance of 316 stainless steel in purified NaCl-MgCl2 eutectic salt at high temperature. (15th April 2020) - Guo, Lili; Liu, Qi; Yin, Huiqin; Pan, T.J.; Tang, Zhongfeng
Highlights: Corrosion behaviors of 316SS were studied in purified NaCl-MgCl2 eutectic salt. Good corrosion resistance of 316SS was found in purified NaCl-MgCl2 at 600°C. 316SS corrosion rate in purified NaCl-MgCl2 was very low even at 700 °C. Corrosion mechanisms of 316SS in purified NaCl-MgCl2 were obtained. Abstract: The effects of temperature on the corrosion of 316 stainless steel (316SS) in purified NaCl-MgCl2 eutectic salt under Ar were investigated through immersion test. The corrosion of samples accelerated and intergranular corrosion became obvious with increased temperature. The corrosion of 316SS was attributed to the selective dissolution of Cr, and corrosion had strong temperature dependence. The corrosion mechanism under the NaCl-MgCl2 eutectic salt was the combined effect of a dissolution mechanism with matrix metal element, which was attributed to the accelerating effect of surface chromium-dissolution and intergranular-diffusion rates with increased molten salt temperature.